PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PENGUNTIT YANG MEMILIKI GANGGUAN KEJIWAAN - Fathya Chalida Umam (Fakultas Hukum Universitas Udayana, 2023)
Regulations regarding the act of stalking have not been explicitly regulated in Indonesia, especially for perpetrators who have mental disorders. For this reason, it is important to examine and analyze the parameters of criminal liability for stalkers who have mental disorders and efforts to prevent them. This research is a normative juridical research using statutory approach and conceptual approach. The data collected is secondary data which is analyzed using qualitative analysis method. Based on the results of this study, the application of criminal liability against stalkers who have mental disorders does refer to Article 44 of the Criminal Code, but the assessment related to the parameters of a person's ability to be responsible is entirely based on evidence at trial which then forms the judge's conviction. As for avoiding the occurrence of stalking, prevention efforts need to be made, namely by not providing personal information to unknown people and limiting conversation responses to new people. Remedial efforts also need to be made, namely through the reform of criminal law policies that can be formulated in the future, so that the act of stalking can be accommodated more clearly and firmly.